PENERAPAN METODE SIMPLEKS UNTUK OPTIMASI MEMINIMALKAN BIAYA PRODUKSI ES BUAH MAROS MENGGUNAKAN QM FOR WINDOWS - Welpison Jr. Wonerengga; Rafli Muhammad. F, Piter Logo, Vasilli Z. P. Jafil, Siors Salak, Ahmad D. A. Ramli; Heru Sutejo (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
The development of MSMEs (Micro, Small, and Medium Enterprises) has significantly increased and has had a considerable impact on the economy. MSMEs play a role in boosting both regional and national economies. Es Buah Maros MSME, which specializes in producing fruit ice, es pisang ijo, and mixed fruit ice, faces challenges in minimizing production costs, including raw materials and working hours, while maintaining a weekly income of IDR 3,000,000. The purpose of this study is to increase the profitability of Es Buah Maros production by reducing raw material costs, working time, and production costs using the Linear Programming method with QM For Windows V5. The linear programming method is used to predict working time, raw material costs, and production costs, with the available production time being 840 minutes. The results of the study show that by using the QM For Windows V5 application and the linear programming method, it is possible to reduce the minimum cost by IDR 280,000 by producing fruit ice as indicated in the solution X1 = 28 (twenty- eight portions) of fruit ice per day, without reducing the weekly income of IDR 3,000,000. The aim is for this production cost efficiency to contribute to making the Es Buah Maros MSME more effective and efficient in its production process while achieving ideal income levels. In this study, the QM For Windows V5 application and the linear programming method were used to predict working time, raw material costs, and production costs by utilizing historical data and statistical analysis. This approach helps make the production process more effective in managing operations without disruptions. The results of this research are expected to help Es Buah Maros MSME minimize production costs without compromising product quality